Management of temporomandibular joint dislocations in the emergency department - a case series (Indian Journal of Case Reports, 2018)
The temporomandibular joint (TMJ) or TMJ is a type of ginglymoarthrodial joint and its articulation involves both sliding and hinge type movements. Dislocation of this joint is a very painful condition and needs acute emergency care. Most of these acute dislocations can be managed by emergency physicians. However, chronic dislocations can be managed with the conservative approach. TMJ disorders are the rare complications in those patients, which are under antiretroviral therapy and until now, there are only few cases reports in the literature. We report three cases of TMJ dislocations that were managed successfully in an emergency room. No conclusive cause-effect relationship has been found linking the TMJ disorders to the human immunodeficiency virus-antiviral treatment.